Analisis Pengaruh Kinerja Keuangan dalam Memprediksi Pertumbuhan Laba - Dindawati; Rimawan, M. (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The purpose of the study to determine and analyze the effect of Debt to Equity Ratio (DER) and Total Asset Turn Over (TATO) on profit growth at PT. Astra Agro Lestari, Tbk. The research method used is an associative quantitative approach with secondary data sources. The population used in this study is the annual financial report data of PT. Astra Agro Lestari, Tbk for 23 years from 1997-2020. The sample in this study is the annual financial report of PT. Astra Agro Lestari, Tbk for the last 10 years, namely from 2010-2019 using purposive sampling technique. The data analysis tool uses classical assumption test, multiple linear regression, correlation coefficient, determination test and hypothesis testing (F test and T test). The results of this study state that the Debt to Equity Ratio (DER) has no significant effect on profit growth at PT. Astra Agro Lestari Tbk, Total Asset Turn Over (TATO) has no significant effect on profit growth at PT. Astra Agro Lestari Tbk and simultaneously Debt to Equity Ratio (DER) and Total Asset Turn Over (TATO) did not significantly affect the growth of PT. Astra Agro Lestari Tbk. It can be seen in the results of the F test that the calculated F value is greater than the F-table value with a significant level greater than 0.05 (0.620 > 0.05) so that Ha is rejected and Ho is accepted, meaning that there is no direct effect between debt to Equity Ratio (DER) and Total Asset Turn Over (TATO) for PT. Astra Agro Lestari Tbk.